Private Cost of Journey to Work Place among Secondary School Teachers in Edo State, Nigeria - Nwadiani, Mon.; Iwerebor, Faith Eseugwenije (NIU Journal of Social Sciences, 2026)
The study investigated the private cost of journey to work place among secondary school teachers in Edo State, Nigeria. Four research questions were raised and one hypothesis formulated that guided this study. The research questions were answered and the hypothesis tested at 0.05 level of significance. The study was a descriptive study that employed the ex-post-facto research design. The population of the study comprised all teachers in the one hundred and twenty-nine (129) public senior secondary schools in the seven (7) Local Government Areas of Edo South Senatorial District and three Local Government Areas representing 43% of the seven Local Government areas in the Senatorial District were randomly selected. Six schools were equally randomly selected representing 10% of the 60 schools in the Local Governments and all the 120 teachers comprised the sample for the study. A questionnaire titled Distance and cost of transportation of a teacher from home to workplace (DCTTHW) was validated and used to elicit data for the study. Percentage and ANOVA were used to analyze the data. The findings of the study revealed that teachers in the senatorial district commute less than 5Km to their workplace using car/bus/taxis as mode of transportation. They spend relatively less amount on transportation. There was a significant difference in their transportation cost along the variables of distance, location and gender. The study therefore recommends that the Ministry of Education should keep appointing/posting teachers within a short distance of their residence or schools close to their homes to reduce private cost.  Keywords: Private Cost, Journey to work place, Transportation Cost.